Archgroup turning imagination into reality . - Archgroup (Mulgrave, Victoria, Australia Images Publishing Group Pty Ltd, 2019)
This monograph showcases the trajectory of an empire built by the sheer dint of its driving success. Archgroup has gained international recognition as a comprehensive service provider in the architectural segment, with special focus being on its prolific and vital role dominating the skyline of the UAE's world-class destination, Dubai. The firm's work has now become synonymous with epithets such as 'tallest', 'highest' and
'longest' across the Gulf region.0Inside, the richly illustrated pages chronicle close to 100 projects by Archgroup, both built and in progress. Each work provides insight into the values, design-thinking and process-orientated approach that is the firm's signature, making this volume a valuable resource that goes beyond the study of the built form to talk about the firm's inimitable ethos that guides its design candour
Includes index
WorldShare provided record
Keywords: Archgroup .; Architecture -- United Arab Emirates -- Dubai .; Dubai (United Arab Emirates) -- Buildings, structures, etc .; Dubai (United Arab Emirates) -- Buildings, structures, etc. -- Pictorial works